2021
DOI: 10.3390/cancers13020338
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Future Directions in Clinical Management of Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the most common cancer arising in the head and neck region. The most common risk factors are smoking, excessive drinking, and human papillomavirus (HPV) infection. While the overall incidence of smoking is decreasing, the incidence of HPV-related HNSCC is increasing in the United States and Western Europe, which led to a shift in understanding of the pathophysiology, treatment, and prognosis of this disease. The outcomes for non-metastatic HNSCC remains very enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 110 publications
0
57
0
1
Order By: Relevance
“…Considering HPV-positive tumors to be immunologically active, in recent past, attempts have been made to design PD1-PDL1 immunotherapeutic strategies ( Qiao et al, 2020 ). New cancer immune-prevention treatments include FDA-approved inhibitory antibodies such as pembrolizumab (anti-PD1 mAb), nivolumab (anti-PD1), and ipilimumab (anti–CTLA-4 mAb) ( Bauman and Ferris, 2014 ; Ferris et al, 2018 ; Mehra et al, 2018 ; Havel et al, 2019 ); co-stimulation and co-inhibition pathways ( Kuss et al, 2003 ; Tsukishiro et al, 2003 ; Baruah et al, 2012 ; Pardoll, 2012 ); and check-point blockade therapy ( Davis et al, 2016 ; Muzaffar et al, 2021 ). A systematic assessment of the cost effectiveness of ICIs showed nivolumab was not cost-effective over chemotherapy for HNC ( Verma et al, 2018 ).…”
Section: Head and Neck Cancer Spectrummentioning
confidence: 99%
“…Considering HPV-positive tumors to be immunologically active, in recent past, attempts have been made to design PD1-PDL1 immunotherapeutic strategies ( Qiao et al, 2020 ). New cancer immune-prevention treatments include FDA-approved inhibitory antibodies such as pembrolizumab (anti-PD1 mAb), nivolumab (anti-PD1), and ipilimumab (anti–CTLA-4 mAb) ( Bauman and Ferris, 2014 ; Ferris et al, 2018 ; Mehra et al, 2018 ; Havel et al, 2019 ); co-stimulation and co-inhibition pathways ( Kuss et al, 2003 ; Tsukishiro et al, 2003 ; Baruah et al, 2012 ; Pardoll, 2012 ); and check-point blockade therapy ( Davis et al, 2016 ; Muzaffar et al, 2021 ). A systematic assessment of the cost effectiveness of ICIs showed nivolumab was not cost-effective over chemotherapy for HNC ( Verma et al, 2018 ).…”
Section: Head and Neck Cancer Spectrummentioning
confidence: 99%
“…Mounting evidence highlight that, in patients diagnosed with locoregionally advanced SCCHN who have been treated with upfront surgery or upfront chemoradiation, the percent of locoregional failure is about 40–50%, while distant failure is 20–30% [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of generation sequencing technology, many researchers have used omics data to predict the occurrence or prognosis of tumors. Studies have shown that the up-regulation and down-regulation of speci c gene expression in serum may be associated with clear diagnosis and prognosis of tumor [6,7].…”
Section: Introductionmentioning
confidence: 99%